Venous thromboembolism: reducing the risk in a Role 3 setting. Issue 4 (15th January 2014) - Craig, Darren G; Adam, M G; Proffitt, A; Parsons, I; Tai, N R; d'Arcy, J L
Abstract : Background: Venous thromboembolism (VTE) represents a significant preventable cause of hospital mortality. VTE assessment and prophylaxis rates are key patient safety and quality of care indicators. The aim of this study was to audit low molecular weight heparin (LMWH) and graduated elasticated compression stockings (GECS) prescriptions compared with the current Clinical Guidelines for Operations. Methods: Complete audit loop in the Role 3 Hospital, Camp Bastion, Afghanistan. A multifaceted intervention programme incorporating physician and nurse education and pre-printed medication charts was introduced to improve VTE assessment and prophylaxis rates. Results: Only 111/301 (36.9%) of patients in the pre-intervention cohort had a VTE risk assessment performed; this improved to 142/155 (91.6%, p<0.0001) post-intervention. A total of 57/88 (64.8%) patients prescribed LMWH pre-intervention had a documented assessment of bleeding risk performed; this rose to 65/66 (98.5%, p=0.0003) post-intervention. In pre-intervention, only 63/213 (29.6%) patients had a documented reassessment of VTE and bleeding risk at 24 h; reassessment rates rose to 68.8% (66/96 patients, p<0.0001) post-intervention. Of those patients at risk of VTE without ongoing bleeding risk, 62/96 (64.6%) had LMWH prescribed pre-intervention; this rose to 57/62 (91.9%) post-intervention (p<0.0001). Inappropriate LMWH prescription rates fell from 26/190 (13.7%) to 4/85 (4.7%, p=0.035) post-intervention. In those patients in whom GECS were not contraindicated, prescription rates rose from 23/95 (24.2%) to 42/62 (67.7%, p<0.0001) post-intervention. Conclusions: Inclusion of pre-printed LMWH/GECS prescriptions and risk assessment stickers in the mediction chart significantly improved rates of VTE risk assessment and prophylaxis. These easily reproducible and low-cost interventions could improve patient safety on deployment.